2007
DOI: 10.1074/jbc.m609750200
|View full text |Cite
|
Sign up to set email alerts
|

Classical Anticytokinins Do Not Interact with Cytokinin Receptors but Inhibit Cyclin-dependent Kinases

Abstract: Cytokinins are a class of plant hormones that regulate the cell cycle and diverse developmental and physiological processes. Several compounds have been identified that antagonize the effects of cytokinins. Based on structural similarities and competitive inhibition, it has been assumed that these anticytokinins act through a common cellular target, namely the cytokinin receptor. Here, we examined directly the possibility that various representative classical anticytokinins inhibit the Arabidopsis cytokinin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The main virulence factors of R. fascians are the fas-encoded cytokinins (Crespi et al, 1992(Crespi et al, , 1994Vereecke et al, 2000;Pertry et al, 2009). Because cytokinins are known to directly regulate cell division at the G2-to-M transition by dephosphorylating CDKs (Zhang et al, 1996(Zhang et al, , 2005Laureys et al, 1998;Spíchal et al, 2007), besides stimulating CDKB1;1 expression, the direct activation of CDKs by the bacterial cytokinins might represent a second level of stimulation at the G2/M checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…The main virulence factors of R. fascians are the fas-encoded cytokinins (Crespi et al, 1992(Crespi et al, , 1994Vereecke et al, 2000;Pertry et al, 2009). Because cytokinins are known to directly regulate cell division at the G2-to-M transition by dephosphorylating CDKs (Zhang et al, 1996(Zhang et al, , 2005Laureys et al, 1998;Spíchal et al, 2007), besides stimulating CDKB1;1 expression, the direct activation of CDKs by the bacterial cytokinins might represent a second level of stimulation at the G2/M checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Froldi et al [9] showed that 6-benzyladenine could act on a purinergic type-2 receptor that induces calcium mobilization in rat atria, suggesting a membrane-bound protein for cytokinins in animal cells. In addition, since cytokinins are important at specific phases of the plant cell cycle [10], in parallel, their anticancer effects were attributed to mediation by cyclins [11] or cyclin-dependent kinases [12], [13], suggesting the potential for cytokinins as anticancer drugs [7]. Thus, cytokinin might be used as a plant hormone and also could possibly serve as a candidate for treating human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In the presented method the validation step is based on the direct confirmation of the hit interaction with the ligand-binding site. However, whatever cytokinin-specific bioassay can be used for the further functional validation of a cytokinin receptor agonist or antagonist as described, e.g., by Doležal et al (2006) and Spíchal et al (2007), respectively.…”
Section: Discussionmentioning
confidence: 99%